Stalin and the Literary Intelligentsia, 1928-39 - Kemp-Welch, A. author. aut Link
VI, 338 p.
Keywords: Stalin's fascination with writers was fully reciprocated as the many 'Odes to Stalin' show. During the 1970s a hugely elaborated system was established for the regulation of belles-lettres based on institutions, ideas and individuals. This original study, ten years in preparation, is based on extensive access to Soviet archives. Much new evidence has been uncovered about the inner workings of cultural policy in the Stalin period and documents by Stalin himself are published for the first time.